Nonsystemic fungal endophytes increase survival but reduce tolerance to simulated herbivory in subarctic Festuca rubra - Santangelo, James S.; Kotanen, Peter M. (Ecosphere, 2016)
This is the publisher's version of an article published by the Ecological Society of America. Plant–microbial symbioses are widespread in nature and can shape the ecology and evolution of hosts and interacting symbionts. Fungal endophytes—fungi that live asymptomatically within plant tissues—are a pervasive group of symbionts well known for their role in mediating host-responses to biotic and abiotic stresses. However, they also may become pathogenic and often impose metabolic costs on hosts. Here, we examine the role of fungal endophytes in mediating responses of the host grass red fescue (Festuca rubra) to salt and herbivore stress. We collected 38 red fescue genotypes from within its native range on Akimiski Island, Nunavut, Canada, where it occurs in the supratidal region on the northern part of the island and is heavily grazed by nesting and brood-rearing snow geese (Chen caerulescens caerulescens) and Canada geese (Branta canadensis). We screened all plants for the presence of the systemic endophyte Epichloë festucae and sequenced the nonsystemic endophytic community on a subset of these plants. While we did not detect E. festucae, our plants instead were host to a diverse array of nonsystemic fungal endophytes. We then conducted a fully factorial greenhouse experiment where we crossed plant genotype (4 levels) with simulated grazing (clipped or unclipped), endophyte status (present or absent) and salinity (0, 32 or 64 ppt) to examine the ecological role of this endophytic community. Overall, the presence of nonsystemic endophytes increased plant survival, but only in the absence of salt or clipping. On the other hand, these endophytes reduced plant tolerance to simulated herbivory by 69% but had no effect on aboveground plant growth. Thus, our results identify a potential nonsystemic endophyte-mediated trade-off in host plant survival and tolerance to herbivory and suggest this trade-off may be altered by stressful abiotic conditions. This research was supported by NSERC with assistance from the Ontario Ministry of Natural Resources.